Synthesis, characterization and chlorination of 2-acrylamido-2methylpropane sulfonic acid sodium salt-based antibacterial hydrogels - Hiçyılmaz, Ayşe Sezer; Seçkin, Abdullah Kemal; Çerkez, İdris (Elsevier Science Bv, 2017)
2-Acrylamido-2-methylpropane sulfonic acid sodium salt-based hydrogels were synthesized by redox polymerization and rendered biocidal by dilute household bleach treatment. The developed hydrogels were characterized by SEM, EDX, FTIR, DSC and TGA. The effect of chlorination parameters on the chlorine loadings and water absorption degree was studied. It was found that depending on the halogenation conditions, the oxidative chlorine loadings could be tuned between 0.10 and 2.82 wt%, and the water absorption degree could be obtained between 10 and 230 g/g. Moreover, the chlorinated hydrogels effectively inactivated about 7 logs of the Gram-positive and Gram-negative bacteria.
Keywords: Hydrogel; Antimicrobial; N-halamine; 2-Acrylamido-2-methylpropane sulfonic acid; sodium salt